Domestic Violence Reflected In Nujood Ali's And Delphine Minoui's I Am Nujood, Age10 And Divorced Memoir (2010) :A Feminist Perspective - Wulandari, Febriana, Dr. Phil. Dewi Candraningrum, S.Pd, M. Ed, Drs. Abdillah Nugroho, M.Hum (2013)
This study is about domestic violence reflected in Nujood Ali's and Delphine Minoui's I am Nujood, Age 10 and Divorced memoir (2010) by using a feminist perspective. The objective of the study is to analyze the memoir based on its structural elements and analyze the memoir based on feminist perspective. The writer uses qualitative method for analyze the memoir. The object of the study is I am Nujood, Age 10 and Divorced Memoir that consist of 11 chapters and 64 pages. It will be analyzed through Feminist Perspective. The primary data is taken from the memoir itself and the secondary data sources are books or any information that are relevant to the subject matter. The technique of the data are reading the novel repeatedly, taking notes of important parts both primary and secondary data, arranging the data into several groups based on its theoretical category, selecting particular parts considered important and relevant for analysis, drawing conclusion and formulate its pedagogical suggestion. The techniques of data analysis are as follows: the first is analyzing the data based on its structural elements, focus will be paid on the structural analysis of the novel, the second step is analyzing the data based in Feminist perspective, focus will be paid on the meaning of domestic violence. The conclusions of the study are, first based on structural analysis of the memoir shows Nujood Ali and Delphine Minoui want to convey a message that the women have their own rights and fundamental freedoms to live which cannot be deprived by anyone. Second, based on Feminist Perspective, this memoir reflect domestic violence by representing feminist issue. Domestic violence is described in this memoir which happens when Nujood lived with her husband; she got physical and mental violence from her husband and her mother-in-law. She got sexual violence from her husband, which was coerced to sex contact, while Nujood's age was still around nine to ten years old. It produces trauma in Nujood's mental.